Prevalence of use of complementary/alternative medicine: a systematic review - E. Ernst (The World Health Organization, 2000)
Reported are the results of a systematic review of the prevalence of use of complementary/alternative medicine. Computerized literature searches were carried out in four databases. Twelve surveys thus found were selected because they dealt with the utilization of complementary/alternative medicine in random or representative samples of the general population. Data were extracted in a predefined, standardized way. Prevalence of use of complementary/alternative medicine ranged from 9% to 65%. Even for a given form of treatment such as chiropractic, as used in the USA, considerable discrepancies emerged. The data suggest that complementary/alternative therapies are used frequently and increasingly. Prevalence of use seemed to depend critically on factors that were poorly controlled in surveys of complementary/alternative medicine. The true prevalence of use of complementary/alternative medicine in the general population remains uncertain.